Storying Contemporary Migration Representation, Aspirations, Advocacy - Englund, Lena.; SpringerLink (Online service) (Cham : Springer Nature Switzerland : Imprint: Palgrave Macmillan, 2024)
This book examines contemporary stories of migration belonging to multiple literary genres such as nonfiction, memoir, novel, and essay, and explores the futures they envision for migrants and their surrounding societies. The primary material ranges from personal experiences of migration for professional purposes and of being undocumented without access to citizenship, to novels that provide fictional representations of migrants and their complex lives. This study asks how migration, as portrayed in contemporary writing, addresses personal, social, and political consequences of being on the move. The book is organised around central themes such as the status of being undocumented, or aspirations and expectations of both migrants themselves as well as their new environs. The material examined has been published from 2016 onwards, addressing the aftermath of the migrant crisis 2015-2016 as well as the Trump administration 2017-2021. Lena Englund is Senior Researcher in the Philosophical Faculty of the University of Eastern Finland, Finland. Her previous books, South African Autobiography as Subjective History: Making Concessions to the Past (2021) and Home and Nation in Anglophone Autobiographies of Africa (2023), were both published by Palgrave Macmillan.
Introduction -- Representing Migration -- Aspirations and Expectations.-Undocumented Migration -- Fortress Europe vs. Open Borders -- Migrant Crisis.-Seeking New Directions.
Accessibility summary: This PDF does not fully comply with PDF/UA standards, but does feature limited screen reader support, bookmarks for easy navigation and searchable, selectable text. Users of assistive technologies may experience difficulty navigating or interpreting content in this document. We recognize the importance of accessibility, and we welcome queries about accessibility for any of our products. If you have a question or an access need, please get in touch with us at accessibilitysupport@springernature.com.
No reading system accessibility options actively disabled
Publisher contact for further accessibility information: accessibilitysupport@springernature.com
Keywords: Creative nonfiction; Emigration and immigration; Literature; Literature, Modern -- 20th century; Literature, Modern -- 21st century; Non-Fiction Literature; Human Migration; World Literature; Contemporary Literature